Socioemotional competencies and behaviour management at school: An exploratory socio-educational intervention - Miguel Ângelo Dias Correia (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
Socioemotional competencies are based on self-knowledge, self-regulation, social awareness, relational skills and responsible decision-making, presenting a close relationship with the efficient management of behaviours in the classroom. In collaboration with 3 schools in the interior of Portugal, an exploratory socio-educational intervention project was developed over a period of 3 months, with the purpose of promoting the socioemotional competencies of 41 primary school children, as a basis for building classroom behaviour management strategies that would facilitate the teachers’ educational action. The intervention involved a process based on collaborative work between teachers, psychologists and educologists, having been able to produce 8 activities that promote socioemotional competencies. Ethnographic procedures, namely, the use of participant observation, field notes and informal interviews, were used to produce scientifically valid and socially useful knowledge. The results show that each activity works on more than one socioemotional skill. The data allowed to outline 6 efficient strategies to manage classroom behaviour. This exploratory project, besides contributing to enriching the educational project of these schools, proved to be a production of knowledge capable of contributing to filling the gap in terms of guidelines for socioemotional education in Portugal based on field evidence.